Methods of use of mycohelminth Aphelenchoides saprophillus for decrease of degree of damage on winter wheat infected with pink snow mold (Fungus mi-crodochium (Fusarium) Nivale (Fr.) Samuels & I.C. Hallet) - A. G. Shchukovskaya; O. B. Tkatchenko; A. A. Shesteperov (Российский паразитологический журнал, 2016)
Pink snow mold of winter wheat is caused by the fungus Microdochium (Fu- sarium) nivale. This disease is widely spread within Russian Federation on grain varieties; its injuriousness is expressed in planting destruction and rather often in total crop failure. In our laboratory experiments the mycohelminth Aphelenchoides saprophillus Franklin was put in number of ±100-200 examples per test tube (20 × 200 mm) on mycelium of fungus M. nivale at temperature 5, 15 and 27 °C. The temperature 5 °C was more favorable for cultivation of mycohelminth A. sapro- phillus on mycelium of fungus M. nivale. At this temperature the reproduction ra- tio of A. saprophillus was 6,5, while mycohelminth was used by whole foods avail- able (mycelia of fungus гриба M. nivale ) within 50-75 days. However at tempera- ture 15 °C the speed of reproduction of A. saprophillus slowed down (reproduction ratio 5,7) that naturally affected the population size. At the end of experiment sin- gle dead species were found in test tubes stored at temperature 15 °C, that cannot be observed in test tubes stored at temperature 5 °C. At the same time reproduction of A. saprophillus was not registered at temperature 27 °C. Methods of cultivation of A. saprophillus allows to create suspension of nematodes containing a large number of species. Applying in autumn water suspension made on the base of A. saprophillus on winter wheat allows to decrease the degree of spread of disease in spring from 65 up to 20,4 % which improves the productivity index of wheat and affect crop improvement